2019
DOI: 10.1101/564633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotion Modulation of the Body-Selective Areas in the Developing Brain

Abstract: Emotions are strongly conveyed by the human body and the ability to recognize emotions from body posture or movement is still developing through childhood and adolescence. To date, there are very few studies exploring how these behavioural observations are paralleled by functional brain development. Furthermore, there are currently no studies exploring the development of emotion modulation in these areas. In the current study, we used functional magnetic resonance imaging (fMRI) to compare the brain activity o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 79 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…expression representation in adults, adolescents, and children, we observed that right hemispheric activity in EBA, FBA, and STS increased across age. However, no difference in these areas and in the amygdalae was seen between age groups when contrasting angry or happy versus neutral body movements [24,110]. A difference in the developmental course of body-selective areas awaits elucidation from a developmental feature approach.…”
Section: How To Discover Midlevel Features?mentioning
confidence: 99%
“…expression representation in adults, adolescents, and children, we observed that right hemispheric activity in EBA, FBA, and STS increased across age. However, no difference in these areas and in the amygdalae was seen between age groups when contrasting angry or happy versus neutral body movements [24,110]. A difference in the developmental course of body-selective areas awaits elucidation from a developmental feature approach.…”
Section: How To Discover Midlevel Features?mentioning
confidence: 99%
“…We already know that several "basic" emotions (happiness, sadness, fear, disgust, anger) can be recognized from static and dynamic stimuli depicting body form and movement (Atkinson, Dittrich, Gemmell, & Young, 2004; de Gelder et al, 2010; de Gelder & Van den Stock, 2011; Gr ezes, Pichon, & de Gelder, 2007;Meijer, 1989;Ross, Polson, & Grosbras, 2012). Furthermore, as in face research, emotional body recognition has been shown to be context dependent (Kret & de Gelder, 2010), shows a protracted developmental trajectory (Boone & Cunningham, 1998;Lagerlof & Djerf, 2009;Ross et al, 2012) and has regions of visual cortex specialized for its recognition and interpretation (de Gelder, Snyder, Greve, Gerard, & Hadjikhani, 2004;Downing, Jiang, Shuman, & Kanwisher, 2001; Kret, Pichon, Gr ezes, & Peelen, Atkinson, Andersson, & Vuilleumier, 2007; de Gelder, Crabbe, & Grosbras, 2014, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that instead of referring to the "body-selective areas" of the visual cortex, the system might be more nuanced than the name implies. Indeed, studies that refer to the "body-selective areas" may be looking at areas of cortex selective to individual body components (e.g., hands, arms) rather than "the body" as a whole (Downing et al, 2001;Peelen & Downing, 2005;Ross et al, 2014Ross et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…While this application remains controversial 82 , several neuroimaging studies on developing brains have not only shown neuroanatomical differences between adults but also demonstrated valid neuroimaging results for children using the adult template 71,[83][84][85] . Moreover, the standard adult SPM template enables us to compare or combine the results of previous studies conducted in adults or across different age groups 72,86,87 .…”
mentioning
confidence: 99%